2018
DOI: 10.3389/fphys.2018.00991
|View full text |Cite
|
Sign up to set email alerts
|

Danhong Injection Enhances the Therapeutic Efficacy of Mesenchymal Stem Cells in Myocardial Infarction by Promoting Angiogenesis

Abstract: Stem cell-based therapies have the potential to dramatically transform the treatment and prognosis of myocardial infarction (MI), and mesenchymal stem cells (MSCs) have been suggested as a promising cell population to ameliorate the heart remodeling in post-MI. However, poor implantation and survival in ischemic myocardium restrict its efficacy and application. In this study, we sought to use the unique mode of action of Chinese medicine to improve this situation. Surrounding the myocardial infarct area, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…Danhong injection (DHI), a traditional Chinese medicine, was extracted from Salviae miltiorrhizae Radix and Carthami tinctorii Flos. The main bioactive constituents in DHI include salvianic acid A, salvianic acid B, protocatechuic aldehyde, and rosmarinic acid [7]. In a previous study, DHI was demonstrated to exert many effects, such as anti-inflammatory, antioxidant, anticoagulatory, hypolipidemic, antiapoptotic, vasodilatory, and angiogenesis-promoting actions [8, 9], and DHI is widely used in the treatment of cerebral ischemia and cardiovascular diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…Danhong injection (DHI), a traditional Chinese medicine, was extracted from Salviae miltiorrhizae Radix and Carthami tinctorii Flos. The main bioactive constituents in DHI include salvianic acid A, salvianic acid B, protocatechuic aldehyde, and rosmarinic acid [7]. In a previous study, DHI was demonstrated to exert many effects, such as anti-inflammatory, antioxidant, anticoagulatory, hypolipidemic, antiapoptotic, vasodilatory, and angiogenesis-promoting actions [8, 9], and DHI is widely used in the treatment of cerebral ischemia and cardiovascular diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…We proposed that THSWD could ameliorate the microenvironment after MI as it not only raised the expression of IGF-1 and bFGF but also enhanced angiogenesis and activated the PI3K/Akt signaling pathway. Recent evidence suggested that Danhong injection enhanced the residence of MSCs in the cardiac tissue, promoted angiogenesis, and reduced myocardial infarct size [45]. We also found that Guanxin Danshen formulation enhanced the effects of MSC transplantation for the treatment of MI [46].…”
Section: Discussionmentioning
confidence: 59%
“…13 Several studies have demonstrated that after intravenous delivery, BM-MSCs migrate to the site of bone or cartilage damage, myocardial infarction, and ischemic cerebral injury. [14][15][16] Although MSCs were initially shown to promote tissue repair by trans-differentiation of specific cell types required to repair damaged tissue, current data suggest paracrine signaling as the primary mediator of the reparative effects of MSCs. 17 Practically, attracting more cells to a damaged tissue would enhance the recovery of the injured tissue because of the increase in paracrine factors.…”
Section: Introductionmentioning
confidence: 99%